2022
DOI: 10.1111/hsc.13977
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the abbreviated Lubben Social Network Scale (LSNS‐6) and its association with self‐rated health amongst older adults in Puerto Rico

Abstract: Social isolation is a well‐established determinant of late‐life well‐being, and it may be particularly relevant for older adults in Puerto Rico following Hurricane María. The abbreviated Lubben Social Network Scale (LSNS‐6) is a widely used measure of social isolation, but it has not been validated with Spanish‐speaking older adults. The objectives of this study were to (1) assess the psychometric properties of a Spanish‐language LSNS‐6 and (2) examine its association with self‐rated health (SRH) and psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 94 publications
2
12
0
Order By: Relevance
“…From the above data analyses, the two‐factor structure of the LSNS‐6 was confirmed with satisfactory goodness of fit, and the factor loadings of the CFA in the friend subscale were also greater than those in the family subscale. These findings are consistent with studies with older adults in Asian cultures, 2,3,28 but an opposite pattern is observed in other cultures 15,29 . This may suggest that friendships may play a more vital role in predicting well‐being in older adults as interactions with friends are usually voluntary, and selectivity can maximise their well‐being 30 …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…From the above data analyses, the two‐factor structure of the LSNS‐6 was confirmed with satisfactory goodness of fit, and the factor loadings of the CFA in the friend subscale were also greater than those in the family subscale. These findings are consistent with studies with older adults in Asian cultures, 2,3,28 but an opposite pattern is observed in other cultures 15,29 . This may suggest that friendships may play a more vital role in predicting well‐being in older adults as interactions with friends are usually voluntary, and selectivity can maximise their well‐being 30 …”
Section: Discussionsupporting
confidence: 86%
“…They were also negatively associated with anxiety symptoms (∣ r ∣s ≥ 0.21, p < 0.001), but positively associated with life satisfaction ( r s ≥ 0.29, p < 0.001) and self‐rated health ( r s ≥ 0.20, p < 0.001). These findings echoed previous studies 15,28 . These findings suggest that LSNS‐6 is a reliable and valid tool to measure social networks in Hong Kong Chinese older adults.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations